Case report: Depressive symptoms of Schizophrenic patients - Pornma, Kitikorn; Soonthonchaiya, Rangsiman (Journal of Medicine and Health Sciences, 2022)
Abstract Schizophrenic patients experience depressive symptoms and negative thoughts about themselves and others, including their surroundings and their futures. This symptom could be found at all stages of the disease, and may result in both physical disorders and mental symptoms, as well as being a major risk factor for suicide. This article reports on two depressed schizophrenic patients in a psychiatric hospital in Bangkok between July and August 2020. The assessment was composed of a psychiatric symptom assessment using the Brief Psychiatric Rating Scale (BPRS), the general information questionnaire, and Depression Assessment for schizophrenic patients using the Calgary Depression Scale for Schizophrenia (CDSS). The study results were reported by case analysis, the depression characteristics of schizophrenic patients, the factors causing depression in schizophrenic patients, and a review of the relevant literature. The results of the study found that both case studies had psychiatric symptom of BPRS scores of 20 and 26, respectively. They were in a state of mild psychosis. The depressive symptoms CDSS score was 18 and 16, respectively. The symptoms of depression were moderate. In both cases, it was found that depressive symptoms were in a maintenance phase. The increase in the depressive symptoms score was associated with a decrease in psychiatric symptom scores. Therefore, it can be concluded that the depressive characteristics of schizophrenic patients includes negative distorted thoughts, and their emotions and feelings toward themselves and others, which occurred after decreased psychiatric symptoms. The contributing factors for depression among schizophrenic patients were an understanding of illness, drug therapy cooperation, duration of illness, side effects of their medication, substance abuse, and social and environmental factors.